Sleep quality in children: questionnaires available in Brazil - Cavalheiro, Maria Gabriela; Corrêa, Camila de Castro; Maximino, Luciana Paula; Weber, Silke Anna Theresa (Sleep Science, 2017)
Introduction The purpose of this paper was to evaluate and compare the questionnaires regarding sleep quality among children aged up to 12 years old, used in the Portuguese language in Brazil.Material and methods A search at the literature databases of Lilacs, Scielo and Pubmed was performed using keywords “sleep quality” and “children”. Selected Articles were analysed for age of the studied population, the number of questions and the issues addressed thereby, who realized the application, the analysis of the results, and content.Results Out of 9377 titles, 11 studies were included, performing 7 different questionnaires: Questionnaire to measure quality of life among children with enlarged palatine and pharyngeal tonsils (translation of OSD-6) (1); Inventory of Sleep Habits for Preschool Children (2); the Questionnaire on Obstructive Sleep Apnoea-18 (OSA-18) (3), Sleep Questionnaire by Reimão and Lefévre - QRL (4); the Questionnaire on Sleep Behaviour Patterns (5) and the translation of the Sleep Disturbance Scale for Children (6); Brief Infant Sleep Questionnaire - BISQ (7) . Six of the questionnaires have covered the following issues: snoring and daytime sleepiness.Conclusions A total of 7 protocols were found to be available in Brazil, the most commonly mentioned being OSA-18 and OSD-6. The use of protocols as a guided interview helps to define diagnosis and treatment among the paediatric population, but its large variability makes it difficult to compare a standardised monitoring process.
Keywords: Child; Surveys and Questionnaires; Quality of Life; Sleep